The Impact of Covid-19 on Financial Structure and Performance: A Comparative Study of Conventional Banks Versus Islamic Banks - Harris, Helmi; Muharram, Harjum (Yayasan Riset dan Pengembangan Intelektual, 2024)
The COVID-19 pandemic that began in 2019 has had a significant impact on the banking sector in Indonesia, both conventional (BUK) and sharia (BUS). This study aims to compare the impact of the COVID-19 pandemic on the financial structure and performance of the two types of banks over three periods: before the pandemic (2017-2019), during the pandemic (2020-2021), and when the pandemic began to decline (January-June 2022). The research method used is quantitative type with secondary data sources from the financial statements of BUK and BUS. The variables analysed include capital adequacy ratio (CAR), non-performing loan ratio (NPL/NPF), loan-to-deposit ratio (LDR/FDR), profitability (ROA and NIM/NI), operational efficiency (BOPO), and third-party fund (DPK) growth. The results showed that the COVID-19 pandemic had a significant impact on the decline in the financial performance of BUK, especially on profitability and operational efficiency ratios. In contrast, BUS showed a higher level of resilience by maintaining stability in several financial indicators of liquidity and operational efficiency. The research concludes that differences in operational systems between BUK and BUS resulted in different responses to the crisis, with BUS being better able to manage risk and financial stability during the pandemic.